An attempt to implement partially premixed combustion strategy in a multi-cylinder CRDI engine: A detailed experimental and wavelet transform analysis. (1st September 2022) - Kumar, Prem; Singh Sandhu, Sarbjot
Highlights: Instead of using a high amount of EGR, a partly premixed combustion strategy is achieved by optimizing the n-butanol/diesel blended fuels and injection timings. Compared to diesel fuel at 2 bar BMEP engine load, DB20 fuel at 8° CA BTDC injection timing achieved low-temperature PPC mode while also reducing NOX (8.08%↓) and smoke (48%↓) emissions. BTE increases when the SOI timing is advanced from 4° CA to 8° CA BTDC and it decreases when the SOI timing is advanced further for all tested fuel under both tested engine load. DB20 possesses lesser cyclic variations with higher frequency (at period 2–6 cycles) intermittent fluctuation in partially premixed combustion at 2 bar BMEP engine load than other tested fuels. Abstract: The main objective of this research was to effectively employ the n-butanol fuel in advanced combustion strategy 'partially premixed combustion (PPC)' and provide the maximum possible replacement of diesel fuel. An experimental study was conducted on a multi-cylinder turbocharged intercooler CRDI engine to optimize the injection timings and diesel/n-butanol blended fuels based on performance, emissions, and combustion characteristics, including cyclic variability, in order to achieve the PPC strategy without compromising thermal efficiency significantly. The combustion characteristics analysis indicate that adding n-butanol fuel into diesel fuel combined with advanced injection (16° CA BTDC) timing leads to a drastic decrease in smoke emission as well as increases in NOX emission than diesel fuel. However, DB20 fuel at 8° CA BTDC injection timing achieved low-temperature PPC mode and reduced NOX (8.08%↓) and smoke (48%↓) emissions simultaneously compared to diesel fuel at 2 bar BMEP engine load. In addition, wavelet power spectrum (WPS) and global wavelet spectrum (GWS) analysis were utilized to investigate the temporal and spectral fluctuations in the partially premixed combustion parameter (indicated mean effective pressure) at optimum injection timing (8° CA BTDC). Results reveal that DB20 possesses lesser cyclic variations with higher frequency (at period 2–6 cycles) intermittent fluctuation in partially premixed combustion at 2 bar BMEP engine load than other tested fuels. A statistical analysis of IMEP variations was also performed to validate the temporal variation in the IMEP time-series signals of the WPS results. The results of WPS could be used to establish an efficient engine control method based on in-cylinder pressure feedback.